Seven new giant pill-millipede species and numerous new records of the genus Zoosphaerium from Madagascar (Diplopoda, Sphaerotheriida, Arthrosphaeridae) - Wesener, Thomas; Sagorny, Christina (European Journal of Taxonomy, 2021)
Seven new species of the giant pill-millipede genus Zoosphaerium Pocock, 1895 are described from Madagascar: Z. nigrum sp. nov., Z. silens sp. nov., Z. ambatovaky sp. nov., Z. beanka sp. nov., Z. voahangy sp. nov., Z. masoala sp. nov. and Z. spinopiligerum sp. nov. All species are described based on drawings and scanning electron microscopy, while genetic barcoding of the COI gene was successful for six of the seven new species. Additional COI barcode information is provided for the first time for Z. album Wesener, 2009 and Z. libidinosum (de Saussure & Zehntner, 1897). Zoosphaerium nigrum sp. nov. and Z. silens sp. nov. belong to the Z. libidinosum species-group, Z. ambatovaky sp. nov. to the Z. coquerelianum species-group, Z. beanka sp. nov., Z. voahangy sp. nov. and Z. masoala sp. nov. to the Z. platylabum species-group and Z. spinopiligerum sp. nov. to the Z. piligerum species-group. Updated identification keys are provided for each species-group. Two western dry forest species, Z. silens sp. nov. and Z. voahangy sp. nov. are recorded from two localities, while the other five species are currently only known from their type localities. Of special conservation concern might be Z. ambatovaky sp. nov. from the lowland rainforest fragment of Ambatovaky, a nowadays isolated lowland rainforest, rapidly shrinking due to slash and burn agriculture. In addition to the new species, new locality data is provided for 11 species and numerous unidentifiable species of Zoosphaerium: Z. neptunus (Butler, 1872), Z. platylabum (de Saussure & Zehntner, 1902) and Z. piligerum (de Saussure & Zehntner, 1897) from the central eastern montane forests, as well as Z. ambrense Wesener, 2009, Z. aureum Wesener, 2009, Z. libidinosum, Z. corystoides Wesener, 2009, Z. discolor Wesener, 2009, Z. smaragdinum Wesener, 2009, Z. villosum Wesener & Sierwald, 2005 and Microsphaerotherium anjozorobe Wesener, 2009.